2018
DOI: 10.3390/ma11081373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Healing Agents on Crack Healing of Asphalt and Asphalt Mortar

Abstract: This study investigated the effect of seven healing agents on crack healing ability of long-term aged asphalt and its mortar. Different healing agents including sunflower oil, aromatic oil, bitumen emulsion, and maltene-based emulsions were used. The crack healing of asphalt made use of two asphalt disk samples and healing was evaluated using direct tensile tests. For asphalt mortar, notched semi-circular samples were used. Test results indicated that the crack healing of asphalt and its mortar depended strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It is concluded that self-healing efficiency of asphalt concrete can be enhanced through microwave heating. Pan et al, [4] investigated the effect of seven healing agents on crack healing ability of long-term aged asphalt and its mortar. Test results indicated that the crack healing of asphalt and its mortar depended strongly on the type of healing agent.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that self-healing efficiency of asphalt concrete can be enhanced through microwave heating. Pan et al, [4] investigated the effect of seven healing agents on crack healing ability of long-term aged asphalt and its mortar. Test results indicated that the crack healing of asphalt and its mortar depended strongly on the type of healing agent.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Wan et al [29], self-healing properties of steel fiber and steel slag based ultra-thin wearing course were studied by a semi-circular bending test under induction heating. Other researches focused on the healing agent effect [30], induced healing efficiency of induction heating and microwave heating [31], and initial self-healing temperature [32].…”
mentioning
confidence: 99%